P-260 Study of kinetic parameters using KIDscoreTMDay5 version 3.0 in euploid, mosaic and aneuploid blastocysts. (30th June 2022) - Pirastu, G; Listorti, I; Manzo, R; Barberi, M; Musella, M; Zazzaro, V; Colasante, A; Varricchio, M.T; Scarselli, F; Mencacci, C; Arrivi, C; Litwicka, K; et al.
Abstract: Study question: Do kinetic parameters change among euploid, mosaic and aneuploid blastocysts? Is the KIDscore TM Day5 version 3.0 (KS-5.3) correlated to preimplantation genetic testing for aneuploidies (PGT-A) results? Summary answer: The KS-5.3 differs in embryo ploidy classes. The analysis of the kinetic variables showed that the aneuploid embryos were significantly slower than euploid and mosaic. What is known already: Chromosomal abnormalities affect more than 50% of embryos in women with >35 years of age and PGT-A is the best way to predict embryo's ploidy status decreasing implantation failure and miscarriage. However, this procedure is not always possible due to social or moral issues. So, the use of the non-invasive time lapse monitoring could be helpful to determine the morphokinetic characteristics in the different ploidy classes. KS-5.3 (vitrolife, Sweden) is a scoring model based on morphokinetic data, developed to predict the pregnancy rate of day-5 blastocysts. Recent publications showed differences in kinetic parameters between euploid and aneuploid embryos. Study design, size, duration: This retrospective study analyzed 728 blastocysts with PGT-A results obtained at Villa Mafalda Clinic from May 2020 to June 2021. Embryos were cultured in EmbryoScope+ time-lapse system (Vitrolife) at 37 °C, 6%CO2, and 5% O2 . The PGT-A was performed using next-generation sequence (NGS) technology on the trophectoderm biopsy sample on day 5/6/7. Automatic annotations for division times and quality gradings were performed by senior embryologists and all kinetic values were reported in hours post microinjection. Participants/materials, setting, methods: 728 blastocysts were classified in: (E) euploid (n = 172), (M) mosaicism (n = 171) and (A) aneuploid (n = 385). In this study, they were considered KS-5.3 and the following kinetic variables: the time to reach 2 cells (t2), 3 cells (t3), 4 cells (t4), 5 cells (t5), and the blastocyst formation (TB). Continuous variables were reported as the median and interquartile range (IQR). For the statistical analysis, nonparametric tests were performed and p < 0.05 was considered statistically significant. Main results and the role of chance: KS5.3 was significantly different between groups [E = 6.6(4.6-7.9) vs M = 5.3(2.9-7.2) vs A = 4.0(2.5-6.6), p < 0.0001]. It was significantly higher in euploid than in mosaic and aneuploid (EvsM p  = 0.0007, EvsA p  <0.0001, MvsA p  = 0.0077). A significant delay in t2, t3, t4 and tb was showed in aneuploid embryos compared to euploid and mosaic, whereas there was no significant difference between euploid and mosaic: [t2: E = 25.80 (24.56-28.09), M = 25.99 (24.49-28.91), A = 27.02 (25.30-29.47), EvsA p  <0.0001, AvsM p  = 0.03, EvsM p  = 0.32]; [t3: E = 37.08 (34.74-39.34), M = 36.69 (34.55-40.02), E = 38.45 (35.93-41.14), EvsA p  = 0.0003, MvsA p  = 0.002, EvsM p >0.99]; [t4: E = 38.28 (35.63-41.19), M = 38.49 (35.47-42.13), A 39.72 (37.25-43.31), EvsA p  = 0.0001, MvsA p  = 0.02, EvsM p  = 0.65]; [tb: E = 107.70 (102.20-114.30), M = 110.10 (103.60-116.80), A = 113.7 (106.80-122.70), EvsA p  <0.0001, MvsA p  <0.0001, EvsM p  = 0.42]. As for t5, there were no differences among the groups. Longer cell cycles in aneuploid embryos could be associated with activated DNA repair mechanism or during chromosome segregation. Instead, regarding the mosaics, there was a significant difference with euploid embryos only in KS5.3. The age was similar between euploid and mosaic [E = 36.29 (33.42-39.00) vs M = 36.71 (34.00-39.33) p  = 0.99], whereas that was significantly higher in aneuploid embryos [A = 39.11(36.01-42.27), EvsA/EvsM p  <0.0001]. Limitations, reasons for caution: All these findings have to be validated in a larger sample size. Furthermore, for the retrospective nature of this study, there were some confounding factors, such as protocol of stimulation, female age, and malefactor. This research did not consider the importance of every single kinetic parameter. Wider implications of the findings: A further study is needed to verify if there is a correlation between morphology and ploidy status. This could clarify the difference in KS-5.3 between euploid and mosaic. In order to decrease age bias, we should enlarge the sample size to analyze a subgroup of patients with higher maternal age. Trial registration number: not applicable